Genetic differences and longevity‐related phenotypes influence lifespan and lifespan variation in a sex‐specific manner in mice. Issue 11 (26th October 2020) - Yuan, Rong; Musters, C. J. M.; Zhu, Yun; Evans, Tracy R.; Sun, Yujie; Chesler, Elissa J.; Peters, Luanne L.; Harrison, David E.; Bartke, Andrzej
Abstract: Epidemiological studies of human longevity found two interesting features, robust advantage of female lifespan and consistent reduction of lifespan variation. To help understand the genetic aspects of these phenomena, the current study examined sex differences and variation of longevity using previously published mouse data sets including data on lifespan, age of puberty, and circulating insulin‐like growth factor 1 (IGF1) levels in 31 inbred strains, data from colonies of nuclear‐receptor‐interacting protein 1 ( Nrip1 ) knockout mice, and a congenic strain, B6.C3H‐Igf1. Looking at the overall data for all inbred strains, the results show no significant difference in lifespan and lifespan variation between sexes; however, considerable differences were found among and within strains. Across strains, lifespan variations of female and male mice are significantly correlated. Strikingly, between sexes, IGF1 levels correlate with the lifespan variation and maximum lifespan in different directions. Female mice with low IGF1 levels have higher variation and extended maximum lifespan. The opposite is detected in males. Compared to domesticated inbred strains, wild‐derived inbred strains have elevated lifespan variation due to increased early deaths in both sexes and extended maximum lifespan in female mice. Intriguingly, the sex differences in survival curves of inbred strains negatively associated with age of female puberty, which is significantly accelerated in domesticated inbred strains compared to wild‐derived strains. In conclusion, this study suggests that genetic factors are involved in the regulation of sexual disparities in lifespan and lifespan variation, and dissecting the mouse genome may provide novel insight into the underlying genetic mechanisms. Abstract : Among inbred strains, the lifespan variations of female and male mice are significantly correlated, suggesting the genetic co‐regulation of lifespan variation between sexes. IGF1 levels associate with lifespan variation and maximum lifespan in a sex‐specific manner. Importantly, female mice with lower IGF1 have longer maximum lifespan, while the male mice with higher IGF1 have longer maximum lifespan.